Pengembangan LKPD Berbasis Inkuiri Terbimbing dan Instrumen Berpikir Kritis pada Pelajaran Kimia Materi Asam Basa - Maktun, Kintan Haiatul; Haris, Mukhtar; Siahaan, Jeckson (FKIP University of Mataram, 2025)
This research aims to develop guided inquiry-based LKPD and critical thinking instruments in acid-base chemistry lessons that are valid and practical. The research uses the R&D (Research and Development) method, a 4D development model which is carried out in only three stages (3D), namely Define, Design, and Develop. The results of the validity test using the Aiken's V index obtained a V value for the LKPD of 0.81 and for the instrument of 0.82, which shows that the LKPD based on guided inquiry and critical thinking instruments on acid-base material are very valid to use. The results of the practicality assessment of the LKPD and instruments showed that the average percentage of the LKPD was 88% and the instrument was 81%, which means that the LKPD based on guided inquiry and critical thinking instruments on acid-base material were very practical to use.Based on these data, it can be concluded that the guided inquiry-based LKPD and critical thinking instruments developed can be used in chemistry learning on acid-base material.